ChemInform Abstract: Catalyst‐Free Synthesis of Skipped Dienes from Phosphorus Ylides, Allylic Carbonates, and Aldehydes via a One‐Pot SN2′ Allylation—Wittig Strategy. Issue 39 (23rd September 2014) - Xu, Silong; Zhu, Shaoying; Shang, Jian; Zhang, Junjie; Tang, Yuhai; Dou, Jianwei
Abstract The regioselective title reaction of stabilized phosphorus ylides with aliphatic and aromatic aldehydes as well as in situ generated ketenes [from (XV)] affords highly functionalized skipped dienes and synthetically important homoallylic allenoates with flexible substitution pattern.